Eros & Arch,. - Frank, Peter; van Kempen, Wink (Amsterdam : Torch Gallery Amsterdam, 1988)
Angermann, Peter ; Bijl, Guillaume ; van Kempen, Wink ; Komar & Melamid ; Kunc, Milan ; Mendini, Alessandro ; Mollino, Carlo ; Zwillinger, Rhonda ; Plumcake ; de Ridder, Willem ; Scholte, Rob ; Tas, Henk ; van den Toorn, Joost ; Vera, Veronica ; Vlugt, Harald ; Weeber, Carel
Eros & Arch, Torch Gallery Amsterdam, 11.06.1988 - 02.07.1988
Engels
boek